School inclusion of children with disabilities in Mozambique: The teachers’ perspective - Franco, Vitor (Frontiers in Education, 2023)
The inclusion of children with special needs is one of the biggest challenges faced by educational systems around the world, corresponding to the UNICEF Sustainable Development Goal (SDG) of ensuring inclusive and equitable quality education and promoting lifelong learning opportunities for all. This process is even more complex process in low-income countries, where the entire education system has significant insufficiencies and support for families with children with disabilities is limited. This present study aims to chart the challenge of implementing inclusive education in Mozambique. Its main objective is to sound the perspectives and expectations of teachers about the education for children with disabilities in their country: a) its advantages and suitability, b) needs, obstacles and difficulties, and c) resources, practices and strategies already used. A qualitative approach was used, with 40 teachers participating in three focus group, submitted later to a content analysis. The results denote the value and importance of moving towards greater inclusion of children with disabilities in Mozambique and increased awareness among teaching staff to uphold the basic right to education, although the conception of inclusion as a distinct special education subsists. Teachers identify multiple needs and difficulties in terms of equipment, resources and practices, and recognize a path that must be continued for inclusion to take place, namely with regard to inclusive public policies and the need for major investment and change in the level of teacher training - which is central to educational transformation.